The Influence of Earnings Management, Corporate Strategy, and the COVID-19 Pandemic on Bankruptcy Risk in Indonesian Retail Companies - Ameralya, Kesya Dwika; Pramesti, Muthia (Universitas Negeri Surabaya, 2024)
COVID-19 pandemic has had a significant impact on retail companies. “Stay at home” policy reduce sales products significantly distributed through retail channels. The potential risk of bankruptcy is a threat to the retail companies existency. This research aims to prove empirically how income smoothing earnings management, company strategy (cost leadership and differentiation), and the COVID-19 pandemic influence bankruptcy risk. This research took a sample of 23 retail trading subsector companies listed on the Indonesia Stock Exchange (IDX) in the first to the fourth quarter of 2019-2020. The method used in this research is Multiple Linear Regression. The results show that income smoothing earnings management has a positive relationship with bankruptcy risk. In addition, if a company implements a cost leadership strategy in its business, it will reduce the risk of bankruptcy borne by the company. On the other hand, differentiation strategy and the COVID-19 pandemic do not have a significant effect on bankruptcy risk.